Malmbanan Diaries - National Research School, APULA (2010)
During an intense four day field trip, a group of nine PhD students and their supervisors – all part of the National Research School for Architecture and Planning in the Urban Landscape, APULA – set out to explore what may be considered the outback of Western Europe’s conurbations, the transnational region of Kiruna - Narvik. Both “remote” and “resourceful”, “threatened” and “thriving” (equally relative notions), this region seemed to offer possibilities to reflect upon many of the current tendencies influencing contemporary planning practice and research. And we were not disappointed. From the very first encounter with the municipality of Kiruna, whose foundation as an urban conglomeration is now literally cracking, to the last glimpses of cosmopolitan Narvik, competing for the cruiser ships’ attention, we found ourselves embedded in a multilayered urban narrative. Following the throbbing of the iron ore carriages running along Malmbanan, the rail link connecting Kiruna, Abisko and Narvik, we tried to get a grasp of what is both “the last wilderness of Europe” and perhaps its most important urban “testing grounds”. The aim of the field trip was to provide ample room for each and every participant to try out, interrogate and reflect upon their different research topics in relation to a totally new setting, as such also linking their subject matters and methods to the general conditions for spatial research. Through journalistic and improvisational approaches, a collaborative map emerged, not only actualizing a shifting and sprawling urbanity, but also the rambling and trailing of research as such. The result of the workshop is the following collaborative diaries; a composite travelogue of a thought provoking passage on the fringes of urbanity. Our guides throughout this dislocation have been Anders Johansson and Erik Wingquist of Testbedstudio, who both generously and enthusiastically shared their experience with us and competently and creatively coordinated the final outcome. Without Anders and Erik we would ...